2011
DOI: 10.1539/joh.o10026
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of DDT and DDE among Malaria Control Workers in the Amazon Region

Abstract: '-DDE). The half-life (mean ± SD) of pp'-DDE was 29.5 ± 22.7 mo. Conclusions: Concentrations of S-DDT/ pp'-DDE in the blood serum of malaria control workers were much higher than levels found in the general population in Brazil and elsewhere. The half-life of pp'-DDE (29.5 mo) estimated for this group of occupationally exposed male adults was shorter than t 1/2 values previously reported for environmentally exposed subjects. (J Occup Health 2011; 53: 115-122) Field Study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…The median half-life of the DDT metabolite p,p'-dichlorodiphenyldichloroethylene (p,p'-DDE) among Brazilian malaria control workers was 28 months, although with large inter-individual variations (Ferreira et al 2011). Using serum from former capacitor workers, Seegal et al found that the geometrical mean halflives over a study period from 1976 to 2004 were 17.8 years for the heavy PCB congeners (i.e., PCBs eluting before DDE using gas chromatography) and 9.6 years for the light congeners (i.e., PCBs eluting after DDE using gas chromatography) (Seegal et al 2011).…”
Section: Responsible Editor: Hongwen Sunmentioning
confidence: 99%
“…The median half-life of the DDT metabolite p,p'-dichlorodiphenyldichloroethylene (p,p'-DDE) among Brazilian malaria control workers was 28 months, although with large inter-individual variations (Ferreira et al 2011). Using serum from former capacitor workers, Seegal et al found that the geometrical mean halflives over a study period from 1976 to 2004 were 17.8 years for the heavy PCB congeners (i.e., PCBs eluting before DDE using gas chromatography) and 9.6 years for the light congeners (i.e., PCBs eluting after DDE using gas chromatography) (Seegal et al 2011).…”
Section: Responsible Editor: Hongwen Sunmentioning
confidence: 99%
“…We used PCB-153 as a biomarker of PCB exposure because concentrations of this PCB congener are relatively high and highly correlated with the total molar concentration of PCBs (Glynn et al 2000; Muckle et al 2001; Needham et al 2011). The elimination half-life of PCB-153 is > 10 years (Ritter et al 2011 and that of p , p ´-DDE, the major metabolite of DDT, is approximately 5 years (Ferreira et al 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Despite regulatory measures and due to their long half-lives, these compounds are still ubiquitous in the environment and detected in a variety of human tissues and fluids (Malisch and Kotz, 2014). The human elimination half-lives of PCB 153, p,p'-DDE, HCB, PFOS and PFOA are > 10 years (Ritter et al, 2011), 5 years (Ferreira et al, 2011),~6 years (To-Figueras et al, 2000), 5 years (Olsen et al, 2007), and 3.5 years (Olsen et al, 2007), respectively. Due to their high lipophilicity (organochlorine compounds) or amphoteric properties (perfluorinated compounds) these compounds are transported via the placenta to the fetus and can also reach the infant through maternal milk (Stefanidou et al, 2009;WHO/UNEP, 2013).…”
Section: Introductionmentioning
confidence: 99%